Linezolid-induced lactic acidosis: the thin line between bacterial and mitochondrial ribosomes. Issue 7 (3rd July 2017) - Santini, Alessandro; Ronchi, Dario; Garbellini, Manuela; Piga, Daniela; Protti, Alessandro
ABSTRACT: Introduction: Linezolid inhibits bacterial growth by targeting bacterial ribosomes and by interfering with bacterial protein synthesis. Lactic acidosis is a rare, but potentially lethal, side effect of linezolid. Areas covered: The pathogenesis of linezolid-induced lactic acidosis is reviewed with special emphasis on aspects relevant to the recognition, prevention and treatment of the syndrome. Expert opinion: Linezolid-induced lactic acidosis reflects the untoward interaction between the drug and mitochondrial ribosomes. The inhibition of mitochondrial protein synthesis diminishes the respiratory chain enzyme content and thus limits aerobic energy production. As a result, anaerobic glycolysis and lactate generation accelerate independently from tissue hypoxia. In the absence of any confirmatory test, linezolid-induced lactic acidosis should be suspected only after exclusion of other, more common, causes of lactic acidosis such as hypoxemia, anemia or low cardiac output. Normal-to-high whole-body oxygen delivery, high venous oxygen saturation and lack of response to interventions that effectively increase tissue oxygen provision all suggest a primary defect in oxygen use at the mitochondrial level. During prolonged therapy with linezolid, blood drug and lactate levels should be regularly monitored. The current standard-of-care treatment of linezolid-induced lactic acidosis consists of drug withdrawal to reverse mitochondrial intoxication and intercurrent life support.